Inovasi dan Strategi Adaptif dalam Pengelolaan Burung Walet untuk Penguatan Ekonomi Desa: Studi di Simpang Datuk : Penelitian - Reliyanti; Haeran; Hasna Dewi; Sitti Fatimah; Nilfatri; Alisyah Pitri; Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Indonesia holds significant potential for the development of the edible bird’s nest industry, particularly in rural areas rich in natural resources and local wisdom. This study aims to examine the management strategies of swiftlet farming in enhancing community income in Simpang Datuk Village, Nipah Panjang Subdistrict, East Tanjung Jabung Regency. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal that management strategies are implemented systematically and adaptively, including the construction of buildings that mimic the natural habitat of swiftlets, the use of acoustic attractants, and pest control measures. These strategies have had a significant impact on increasing community income, although the outcomes vary depending on the effectiveness of individual management practices. The study also highlights the importance of integrating spiritual values and Islamic business ethics, as well as the need for mitigation of inhibiting factors such as pests and environmental disturbances. These findings present a novel contribution by integrating local, technical, social, and spiritual approaches, and may serve as a foundation for the formulation of equitable and sustainable policy development in the bird’s nest industry.